STUDY OF TIMBER MARKET OF MALAYSIA AND ITS IMPACT ON THE ECONOMY AND EMPLOYMENT - Umachandran, Dr. Krishnan; Sawicka, Barbara (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
This article presents the state of the global wood markets, which shows the evolution of forest resources and margins on the timber market over time. The underlying case has been discussed and discussed. Alternative scenarios are presented that allow one to consider some important questions about the behavior of the wood market and the future supply of industrial wood. (1) What happens along the northern and tropical margin? (2) What is the role of wood plantations? and (3) How should management change in the Malaysian market change? The baseline situation suggests that both prices and crop communities are growing in 150 years, with the largest harvest coming from existing and emerging plantations. Future harvest returns will result mainly from intensified management, through additional plantation and higher levels of management in selected forests rather than higher yields in inaccessible forests. Prices and harvest are most sensitive to alternative needs (paper, firewood) and scenarios for creating new plantations and less vulnerable to the costs of access to remote forests.